Metformin synergistic pemetrexed suppresses non‐small‐cell lung cancer cell proliferation and invasion in vitro. (18th July 2017) - Zhang, Yan; Feng, Xiuli; Li, Tao; Yi, Erpan; Li, Yu
Abstract: The aim of this study was to investigate whether metformin in combination with pemetrexed has an effect on the treatment of non‐small‐cell lung cancer (NSCLC) models and to explore the related molecular mechanism. The half maximal inhibitory concentration (IC50) and combination index (CI) of metformin and pemetrexed were detected by the CCK8 assay to assess the antiproliferative and therapeutic effects of the two‐drug combination. Flow cytometry (FCM) and invasion assays were used to estimate the variation in apoptosis rate and invasion ability of the differently treated NSCLC cell lines. Apoptotic markers were detected by western blotting to validate the data related to the antiproliferation and proapoptosis effects. Metformin monotherapy inhibited the growth of NSCLC cell lines and reduced the invasion ability to different degrees compared with the control groups ( P < 0.05). Metformin in combination with pemetrexed produced a synergistic effect (CI < 0.90) compared with the two drugs in monotherapy in the three tested NSCLC cell lines. Metformin in combination with pemetrexed significantly increased the cell numbers of HCC827 cells at S phase ( P < 0.001), and the combination therapy had no influence on the A549 and H1975 cell lines. We found that combining metformin with pemetrexed induced more cell apoptosis than metformin or pemetrexed used alone ( P < 0.05), which was validated by the apoptotic markers. These results demonstrate that the combination of metformin and pemetrexed has a synergistic effect on the treatment of NSCLC cell lines by inducing apoptosis or blocking the cell cycle. Our data indicate that the combination of metformin and pemetrexed could have beneficial antitumor effects on NSCLC cells in vitro. Abstract : These results demonstrate that the combination of metformin and pemetrexed has a synergistic effect on the treatment of NSCLC cell lines by inducing apoptosis or blocking the cell cycle. Our data indicate that the combination of metformin and pemetrexed could have beneficial antitumor effects on NSCLC cells in vitro.